Clima laboral y su relación con la satisfacción de los trabajadores de la Municipalidad Provincial de Requena 2020 - De la Cruz Torres, Gabriela del Carmen (2023)
The main objective of the research was to establish the relationship between the work environment and the satisfaction of workers in the Provincial Municipality of Requena, 2020. With an applied type study method, correlation level and non-experimental design, conformed by a population of 467 people, obtaining a sample of 206 workers to whom a survey was applied as a technique and a questionnaire as an instrument for collecting the corresponding information. Therefore, the work environment of the workers of the Municipality is qualified as regular (26%). On the other hand, worker satisfaction is average (28%). Then the correlations were determined, that is, there is a significant relationship between work environment and worker satisfaction, corroborated by a coefficient and a sig of (r = 0.754; p = 0.000) positive considerable. Also, for individual environment a coefficient and a gis of (r = 0.671; p = 0.000) positive mean. For organizational environment a coefficient and a gis of (r = 0.688; p = 0.000) positive mean. All results are significantly related to worker satisfaction.